2011
DOI: 10.1128/jcm.01556-10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Enterotoxigenic Bacteroides fragilis Subtypes Isolated from Children with and without Diarrhea

Abstract: A rapid real-time PCR (RT-PCR) approach was developed to detect the bft gene subtypes in Bacteroides fragilis isolated from fecal samples. DNA obtained from diarrhea (110) and nondiarrhea (150) samples was evaluated. Subtype 1 was observed in 9 (8.2%) diarrhea and 7 (4.7%) nondiarrhea samples. Subtype 2 was not detected in any DNA samples, and subtype 3 was observed in only 1 diarrhea sample. The presence of the bft-1 gene did not show any statistically significant differences between the groups of children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…Although the incidence of CRC was reported lower in Iran compared to other countries, its rate was anticipated to increase in the future (Hosseini et al, 2004;Malekzadeh et al, 2009). In previous studies, it was also reported that ETBF may have a role in diarrhea and IBD (Myers et al, 1987;Prindiville et al, 2000;Basset et al, 2004;Merino et al, 2011;Purcell et al, 2017;Zamani et al, 2017). Some investigations have suggested that certain bacterial species (e.g., ETBF) may operate as pathogenic bacteria that clarify the development of dysbiosis in microbial community of the gut and trigger CRC (Hajishengallis et al, 2012;Hajishengallis and Lamont, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the incidence of CRC was reported lower in Iran compared to other countries, its rate was anticipated to increase in the future (Hosseini et al, 2004;Malekzadeh et al, 2009). In previous studies, it was also reported that ETBF may have a role in diarrhea and IBD (Myers et al, 1987;Prindiville et al, 2000;Basset et al, 2004;Merino et al, 2011;Purcell et al, 2017;Zamani et al, 2017). Some investigations have suggested that certain bacterial species (e.g., ETBF) may operate as pathogenic bacteria that clarify the development of dysbiosis in microbial community of the gut and trigger CRC (Hajishengallis et al, 2012;Hajishengallis and Lamont, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…All the primers and probes used for the detection of all bft gene types had been designed in our previous study (Zamani et al, 2017). In order to detect the bft gene subtypes, the real-time PCR was performed as previously described (Merino et al, 2011).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…B. fragilis represents a common cause of endogenous infections in humans that is frequently associated with polymicrobial infections such as intra-abdominal, diabetic foot, obstetric-gynecologic tract and surgical site infections, as well as toxin-dependent diarrhea in adults and children (7, 8). Enterotoxigenic Bacteroides fragilis (ETBF) induced diarrhea in children has been reported by different researchers in various parts of the world, but ETBF has also been found in non-diarrheal fecal samples (9, 10). …”
Section: Introductionmentioning
confidence: 99%
“…In that respect, molecular assays, given their fast turnaround times and high sensitivities, could facilitate a better diagnostic procedure. Studies on PCR-based detection of B. fragilis have focused on enterotoxigenic strains in fecal specimens (4)(5)(6)(7) or as an indicator of water contamination (8)(9)(10). In contrast, detection of B. fragilis in general clinical practice, using either conventional PCR (C-PCR) (11,12) or real-time PCR (RT-PCR) (13), is limited.…”
mentioning
confidence: 99%